Transports of Translation: Creativity and Healing - Sara GREAVES (E-REA)
Along with the numerous cultural, religious or political functions of translation (establishing religious authority or nation-building, for instance, as with the King James Version of the Bible), along with its didactic use in language-learning and its intercultural one in aesthetic transmission and appropriation, translation can also play a healing role. Bi- or plurilingual speakers and language students often experience difficulties of various kinds, including insecurity in one of the languages, unintentional code-switching and “attacks” of awkward, embarrassing untranslatability, or conflicts of loyalty due to the “inferior” status of the mother tongue. Children who cannot translate their experience of school into the language spoken in their home, or their “interior language” (De Mattia-Viviès) for instance, or plurilingual parents unable to translate the symptoms of their child for the psychiatrist, as well as students learning foreign languages, can all benefit from the transports of translation. The polysemy of the term “transport” – both conveyance from one place to another and “an intense exaltation of mind and feelings” that “lifts one out of oneself” (Merriam-Webster Dictionary), will help us conceptualise the pedagogic and therapeutic value of practising translation. This short article will look at creative translation workshops as a means to vindicate all languages, to heal conflicted identities by facilitating and fluidifying movement between languages.